Digital Nomads in Peniche: Exploring the Relation between Remote Work and Surfing - Baptista, Rui Gonçalo Timóteo (2024)
The current study investigates the dynamics of digital nomadism within the surf-centric locale of Peniche (Portugal). It explores how the convergence of remote work and the surf lifestyle influences digital nomads' choice of Peniche as a destination, their integration into local communities, and their contribution to sustainable tourism. This research examines the connection between digital nomadism and surf culture in Peniche, highlighting how the integration of work and leisure shapes the lifestyle and preferences of digital nomads — adopting a mixed-methods approach, including an online survey and a focus group discussion. The results explore digital nomads' motivations, lifestyle choices, and community engagement, with a particular emphasis on their involvement in surfing activities. The findings reveal a significant interest in surfing as a lifestyle choice, though not statically significant enough to prove their decision to stay in Peniche. Central to this exploration is the concept of "workcation," a modern adaptation of work and vacation, where digital nomads balance professional commitments and the pursuit of leisure. The study reveals a community valuing flexibility, connections, and sustainable living while pointing out the critical need for improved infrastructure and services to accommodate this demographic better. These insights contribute to the broader understanding of digital nomadism and offer valuable recommendations for local stakeholders in Peniche to foster a more supportive environment for digital nomads, thereby promoting sustainable tourism and community development. This work lays the groundwork for future research on work-leisure integration and its implications for destination marketing and urban planning in surf tourism destinations. Significantly, this discussion extends beyond mere amenities to encompass the strategic use of events like the World Surfing League, which, if leveraged effectively, could substantially strengthen Peniche's position on the global stage as a premier destination for digital nomads.